2021
DOI: 10.3233/jifs-219032
|View full text |Cite
|
Sign up to set email alerts
|

Current situation and development direction of sports industry in colleges and universities based on euclidean algorithm

Abstract: With the development of sports in colleges and universities, the research on innovation reform of sports industry has been deepened. Therefore, based on the above situation, a study of the status quo and development direction of sports industry in colleges and universities based on the Euclid algorithm is proposed. In the research here, according to the traditional sports industry concept to sum up, and then according to the advantages of computer technology to deal with the relevant data. In order to realize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…It is proposed that AFSA is used to solve the path problem of the vehicle with return trip, which can reflect the individual performance function of artificial fish and the three classic behaviors of artificial fish: foraging, clustering and rear-end pursuit, all of which are applied to the path optimization problem [22]. The artificial fish swarm algorithm is combined with the nuclear fuzzy C-means algorithm, and has been successfully applied to wine quality classification [23]. A cluster analysis algorithm based on artificial fish swarm algorithm is proposed and successfully applied to regional economic analysis [24].…”
Section: Related Workmentioning
confidence: 99%
“…It is proposed that AFSA is used to solve the path problem of the vehicle with return trip, which can reflect the individual performance function of artificial fish and the three classic behaviors of artificial fish: foraging, clustering and rear-end pursuit, all of which are applied to the path optimization problem [22]. The artificial fish swarm algorithm is combined with the nuclear fuzzy C-means algorithm, and has been successfully applied to wine quality classification [23]. A cluster analysis algorithm based on artificial fish swarm algorithm is proposed and successfully applied to regional economic analysis [24].…”
Section: Related Workmentioning
confidence: 99%
“…Competitive sports, for example, have generated substantial amounts of data, presenting new opportunities for advancement. By collecting and calculating the game data to establish a simulation database, the team can provide the best tactics [4][5]. 2, the current proportion of the population participating in sports in China stands at 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The sports industry's specificity and complexity require a reasonable adjustment and upgrade of its structure to achieve long-term sustainable economic growth. By studying the inner law of the structural change of the sports industry, a reasonable industrial layout and development direction can be revealed so as to promote the optimal allocation of resources and the improvement of economic efficiency and to promote the development and upgrading of the sports industry [7][8]. Therefore, an in-depth study of the relationship between structural upgrading of the sports industry and economic growth is of great significance for promoting the development of the sports industry and facilitating economic growth.…”
Section: Introductionmentioning
confidence: 99%